Odwołalność czynności cofnięcia skargi do wojewódzkiego sądu administracyjnego - Malinowski, Piotr Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The withdrawal of a complaint to the administrative court refers to the main procedural act of the process before the administrative court, which initiates the process of judicial review of the legality of the action, inaction or excessive length of proceedings before the public administration.The withdrawal of a complaint to the administrative court is a procedural act of the complainant, who is defending his legal interest. The withdrawal of a complaint incorporates a statement of resignation from the protection of individual public rights before the administrative court.Protection of individual interest before the administrative court and the model of administrative justice which is focused not only on the protection of an objective legal order, but also individual public rights, require an analysis of the withdrawal of a complaint to the administrative court, which also includes the issue of revocation of the withdrawal of a complaint to the administrative court.The issue of the legal admissibility of revocation of the withdrawal of a complaint to the court has a fundamental significance for the determination of the legal limit of constitutional human rights to the court. This problem is more complicated and concerns the issue of the legal limits of the protection of individual interest before the court and the objective legal order within the institution to the withdrawal of a complaint to WSA and its importance from the point of view of the function of administrative justice and human rights to the court.
Keywords: czynność procesowa; skarga; proces prawny; sąd; administracja; charakter fakultatywny; usuwalność